Human-Umbilical Cord-Mesenchymal Stem Cells (hUC-MCSs) Therapy with Extravesicles (EVs) Booster Improves Recovery in Type 2 Diabetes Mellitus with Cardiovascular Disease - Nugraha, Dendi Krisna; Jutadi; Anggoro, Naufal Sebastian; Sari, Fikriya Novita; Ardani, Yanuar (Stem Cell and Cancer Research (SCCR), 2025)
Background: Type 2 diabetes (T2DM) is a chronic metabolic disorder characterized by insulin resistance and β-cell dysfunction, leading to persistent hyperglycemia and complications. Studies have explored mesenchymal stem cell (MSC)-based therapies and their extracellular vesicles (EVs) as novel approaches for metabolic regulation and tissue repair. Case: A 43-year-old male patient exhibited symptoms including excessive thirst and hunger, frequent urination, fatigue, and intermittent blurry vision. He had type 2 diabetes and recently worsened symptoms. The obese patient had elevated blood glucose, HbA1c, triglycerides, and uric acid. He received umbilical cord-derived mesenchymal stem cells (161,6 × 106 cells), followed by seven intramuscular EV injections (1.5 cc each), along with diet and antioxidant supplements. Results: Three months after the conclusion of treatment, laboratory test showed significant improvement, with fasting glucose levels measuring at 91 mg/dL, HbA1c levels at 5,1%, triglyceride levels at 151 mg/dL, uric acid levels at 4,9 mg/dL, and an erythrocyte sedimentation rate of 12 mm/hr. The clinical symptoms such as nocturia, fatigue, and neuropathic pain, demonstrated a substantial improvement, as well as led to the resolution of skin xerosis and heel fissures. Conclusion: This case suggests that combined UC-MSC and EV therapy, complemented by lifestyle modification, may contribute to metabolic stabilization and symptomatic relief in T2DM patients.